1997
DOI: 10.1006/viro.1997.8878
|View full text |Cite
|
Sign up to set email alerts
|

Replicon-Helper Systems from Attenuated Venezuelan Equine Encephalitis Virus: Expression of Heterologous Genesin Vitroand Immunization against Heterologous Pathogensin Vivo

Abstract: A replicon vaccine vector system was developed from an attenuated strain of Venezuelan equine encephalitis virus (VEE). The replicon RNA consists of the cis-acting 5' and 3' ends of the VEE genome, the complete nonstructural protein gene region, and the subgenomic 26S promoter. The genes encoding the VEE structural proteins were replaced with the influenza virus hemagglutinin (HA) or the Lassa virus nucleocapsid (N) gene, and upon transfection into eukaryotic cells by electroporation, these replicon RNAs direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
532
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 418 publications
(543 citation statements)
references
References 47 publications
6
532
1
4
Order By: Relevance
“…VRP were produced using a modification of previously described methods [16,17]. Purified DNA plasmids were linearized by NotI endonuclease digestion and used as templates for in vitro RNA transcription using RNA Express T7 kits (Promega, Madison, WI).…”
Section: Vrp Production and Characterizationmentioning
confidence: 99%
“…VRP were produced using a modification of previously described methods [16,17]. Purified DNA plasmids were linearized by NotI endonuclease digestion and used as templates for in vitro RNA transcription using RNA Express T7 kits (Promega, Madison, WI).…”
Section: Vrp Production and Characterizationmentioning
confidence: 99%
“…Pushko et al have demonstrated that when a heterologous gene encoding influenza hemagglutanin (HA) or the Lassa virus nucleocapsid (N) is substituted for the VEE structural proteins followed by transfection into eukaryotic cells, the replicon system can express high levels of HA or N proteins [44]. When packaged into virus-like particles, these replicons have Development of vaccines for prevention of botulismalso been found to induce potent immune responses in inoculated animals against the heterologous proteins, and to protect animals against challenge with the heterologous virus.…”
Section: Other Strategies For Developing a Bont Vaccinementioning
confidence: 99%
“…VRP were produced by electroporation of Vero cells with replicon RNA and two helper RNAs, encoding the Venezuelan equine encephalitis (VEE) virus structural proteins, using modifications of previously described methods [16,17]. VRP concentration, expressed as infectious units (IU) per mL, was determined by an immunofluorescence assay in which serial dilutions of VRP were added to Vero cell monolayers, cultured overnight, reacted with goat anti-gB or anti-pp65 antibody [12] followed by fluorescein isothiocyanate-labeled anti-goat antibody to detect cells expressing the CMV protein.…”
Section: Vrp Productionmentioning
confidence: 99%